Characteristics of hydroxyapatite-reduced graphene oxide composite powders synthesized via hydrothermal method in the absence and presence of diethylene glycol - Hassan Nosrati; Rasoul Sarraf-Mamoory; Maria Canillas Perez; Dang Quang Svend Le; Reza Zolfaghari Emameh; Cody Eric Bünger (Open Ceramics, 2021)
The synthesis of nanocomposites containing hydroxyapatite and graphene sheets has received much attention recently. Therefore, strategies that improve their properties will be useful. The aim of this study was to investigate the effect of diethylene glycol on the characteristics of hydroxyapatite-reduced graphene oxide powders synthesized by a hydrothermal method (180 ​°C, 5 ​h) and the nanocomposites obtained by spark plasma sintering (950 ​°C, 50 ​MPa). Graphene oxide, calcium nitrate tetrahydrate and diammonium hydrogenphosphate were used as precursors. The characterization methods included electron microscopy, X-ray diffraction, Raman spectroscopy, and indentation technique. Obtained results have shown that the presence of diethylene glycol reduced the average size of hydroxyapatite crystallites from 27 to 16 nm, reduced the particle size distribution, and increased the graphene oxide reduction rate. The presence of diethylene glycol during the synthesis process increased the elastic modulus (from 116.4 ​± ​4.9 to 125 ​± ​3.8 ​GPa), hardness (from 4.08 ​± ​0.7 to 6.32 ​± ​0.4 ​GPa), and fracture toughness (from 1.66 ​± ​0.7 to 1.87 ​± ​0.9 ​MPa ​m0.5) of the composite.